Betamethasone augments the antifungal effect of menadione—towards a novel anti‐Candida albicans combination therapy. (24th February 2015) - Jakab, Ágnes; Emri, Tamás; Sipos, Lilla; Kiss, Ágnes; Kovács, Renátó; Dombrádi, Viktor; Kemény‐Beke, Ádám; Balla, József; Majoros, László; Pócsi, István
<x xml:space="preserve">Abstract</x> The fluorinated glucocorticoid betamethasone stimulated both the extracellular phospholipase production and hypha formation of the opportunistic human pathogen Candida albicans and also decreased the efficiency of the polyene antimycotics amphotericin B and nystatin against C. albicans in a dose‐dependent manner. Importantly, betamethasone increased synergistically the anti‐Candida activity of the oxidative stress generating agent menadione, which may be exploited in future combination therapies to prevent or cure C. albicans infections, in the field of dermatology.